Consumer Confidence and Economic Indicators: A Macro Perspective - Hardi, Irsan; Ray, Samrat; Duwal, Niroj; Idroes, Ghalieb Mutig; Mardayanti, Ulfa (Indatu Journal of Management and Accounting, 2024)
This study examines the impact of the determinants of consumer confidence in Indonesia, one of the largest consumer markets in the world. Various macroeconomic factors are assessed, including economic growth, government expenditure, the consumer price index, interest rates, unemployment, and stock price index, using monthly data from January 2009 to December 2022. The study employs the Autoregressive Distributed Lag (ARDL) model as the primary method, with robustness checks using Fully Modified Ordinary Least Squares (FMOLS) and Canonical Cointegrating Regressions (CCR). The results indicate that all selected factors significantly influence consumer confidence, particularly from a long-term perspective. Economic growth and unemployment have a positive impact, while government expenditure, the consumer price index, interest rates, and stock prices exert a negative effect. These findings suggest that businesses should align their strategies with economic trends to capitalize on periods of strong consumer sentiment and mitigate risks during downturns. Simultaneously, policymakers should prioritize effectively managing key macroeconomic factors to sustain and enhance overall consumer confidence.